SUSTAINABLE FINANCE AND THE COST OF CAPITAL: EMPIRICAL EVIDENCE FROM ESG COMPLIANT FIRMS - Moridu, Irwan (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the relationship between compliance with Environmental, Social, and Governance (ESG) principles and firms’ cost of capital. Although ESG is theoretically associated with lower cost of capital through reduced risk perception, empirical findings show varying results depending on industry sector and institutional context. Using a narrative literature review approach, this study analyzes empirical studies from 2010 to 2025 obtained from various indexed databases. The results show that ESG, especially the governance dimension, is consistently negatively correlated with cost of capital, while the influence of environmental and social aspects is contextual. The effect of ESG tends to be stronger in high-risk industries and in countries with strict ESG regulations. This study confirms the importance of ESG as a financial strategy, while strengthening the relevance of Signaling, Stakeholder, and Institutional theories in understanding these dynamics.